From venom peptides to neurotherapeutics: BmK defensins and short-chain peptides as modulators of ion channels - Dong, Yin; Wang, Jiajun; Zhu, Yudan; Zhao, Lu; Zeng, Yunqing; Tang, Lele; Xiao, Qian; Cheng, Jiwei; Wang, Chao; Tao, Jie (Frontiers in Pharmacology, 2026)
Scorpions, having inhabited the Earth long before the emergence of humans, represent an ancient lineage of arthropods. While often regarded with fear due to their potential to induce severe pain or fatal envenomation, scorpion venoms constitute complex cocktails of bioactive molecules known as toxins. Notably, these toxic components have been repurposed in medical research as valuable sources for therapeutic development. In traditional Chinese medicine (TCM), the venom of Buthus martensii Karsch (BmK), commonly referred to as the Chinese scorpion, has been historically employed in the treatment of various neurological disorders, including epilepsy, stroke, glioma, and pain. The principal bioactive constituents of BmK venom are polypeptides that selectively target membrane ion channels. Among these, defensins and short-chain toxins (28–40 amino acids in length) have been identified as key modulators of potassium channels, TRP channels, and chloride channels. These short-chain peptides exhibit several distinct pharmacological advantages, including efficient tissue penetration due to their low molecular mass, remarkable target specificity for particular ion channel isoforms or states, inherently low immunogenicity, and considerable structural versatility that facilitates engineering (e.g., fusion strategies, point mutations) to optimize pharmacokinetics and pharmacodynamics. As such, they represent promising molecular scaffolds for drug design aimed at addressing unmet clinical needs in neurology. We summarize the most advanced drug candidates derived from BmK defensins and short-chain toxins, which exhibit activity against Kv1.3, BK, TRPV1, and other channels implicated in epilepsy, neuroinflammation, glioma, and pain. Structural and functional insights into these peptides reveal mechanisms underlying their target specificity and pharmacological advantages, such as blood–brain barrier penetration and low immunogenicity. This review underscores the originality of BmK peptides as molecular tools and lead compounds for next-generation neurology therapeutics, providing a focused resource for researchers in ion channel pharmacology and peptide-based drug design.